The efficiency of root canal disinfection using a diode laser: In vitro study - Anjali Kaiwar; H L Usha; N Meena; P Ashwini; Chethana S Murthy (Wolters Kluwer Medknow Publications, 2013)
Aims: The aim of this study is to verify the disinfection of diode laser, following chemo-mechanical procedures against Enterococcus fecalis. Materials and Methods: Crowns of 30 extracted premolar teeth were sectioned at the cemento- enamel junction. The canals were shaped using step-back technique to K-file #40. The teeth were randomly assigned to three groups and placed into nutrient broth containing bacterial suspension of Enterococcus fecalis. Group A received no laser radiation. Specimens of group B and C were treated with diode laser (Sirona) with energy set at 1.5 and 3 W, respectively. After laser irradiation, the teeth were placed in vials, which contained 2 mL of the nutrient broth. The vials were incubated at 37°C for 24 h. Grown colonies were identified by standard methods. Statistical Analysis Used: Statistical analysis used was the nonparametric Kruskal-Wallis test, with comparison using the Bonferroni methods of means. Results: Higher mean CFU/mL is recorded in Group A (without laser disinfection) followed by Group B (with 1.5 W laser disinfection) and Group C (with 3 W laser disinfection), respectively. The difference in CFU/mL between the three groups is found to be statistically significant ( P < 0.001). Conclusions: The results of this research show that the 980 nm diode laser can eliminate bacteria that has immigrated into dentin, thus being able to increase the success rate in endodontic therapy.